Phthalocyanine@MXene based hybrid composite materials for flexible supercapacitor applications - Kayir, Nisa; Artar, Emirhan; Unal, Bayram; Gorduk, Ozge; Sahin, Yucel; Gorduk, Semih (ELSEVIER, 2026)
In this study, MXene-based advanced composite electrode materials functionalized with metallo phthalocyanines (CoPc and NiPc) were successfully synthesized and were characterized by different techniques, and their electrochemical performances were evaluated for flexible supercapacitor applications. The extended it-conjugated systems, central metal ions, and specifically designed carboxylic acid groups of the phthalocyanines have enabled strong molecular interactions with the MXene surface. These interactions enhance both electrical conductivity and capacitive properties. Electrochemical measurements revealed that NiPc@MXene and CoPc@MXene flexible electrodes exhibit high specific capacitance values of 669 mF/cm2 (134 F/g) and 556 mF/cm2 (112 F/g), respectively. Furthermore, the electrodes exhibited excellent long-term electrochemical stability, with their initial capacitance retained even after 5000 charge-discharge cycles. This study introduces an innovative strategy for designing advanced MXene-based materials for flexible energy storage applications.
Keywords: Energy storage; Flexible supercapacitor; Hybrid material; MXene; Phthalocyanine; ELECTRODE MATERIAL; X-RAY; CAPACITANCE; NANOHYBRID; NANOSHEETS; CARBON; NI; Chemistry